The Berenstain bears go to camp - "Berenstain, Stan" (Random House: New York, 1982)
The Berenstain cubs enjoy day camp, although they are dubious about the end-of-season pow-wow and sleep-out at the top of Skull Rock
Keywords: Bears Fiction